Awards Before and After the Nobel Prize: A Matthew Effect and/or a Ticket to one's own Funeral? - Ho Fai Chan; Laura Gleeson; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2013)
This study explores whether awards breed further awards and what happens after a researcher receives the Nobel Prize. We therefore collected data on all the 1901 to 1980 Nobel laureates in physics, chemistry and medicine or physiology, looking at the number of awards received each year for 50 years before and after obtaining the Nobel Prize. The results indicate an increasing rate of awards before the Nobel Prize, reaching the summit precisely in the year of the Nobel Prize. After this pinnacle year, awards drop sharply. Such a result is also confirmed when looking at the three different disciplines separately and when conducting a random-effects negative binomial regression model. Moreover, Nobel laureates in medicine or physiology generate more awards shortly before and after the Nobel Prize while laureates in Chemistry attract more awards as time progresses.
Keywords: M52; J33; Z13; 330; Nobel prize; Nobel laureates; Matthew effect; awards; recognition